Identification of Fungi Associated with Grapevine Decline in Castilla y León (Spain) - Martin, M.T.; Cobos, R. (Phytopathologia Mediterranea, 2007)
A number of phytopathogenic fungal species are associated with grapevine decline. Esca, eutypa dieback, black dead arm, and other grapevine decline diseases affecting vine wood have a worldwide distribution. The external symptoms of these diseases, however, can be erratic; even asymptomatic infections are known. Grapevine decline causes economic losses, the size of which depends on factors that still remain unclear, but in all cases the productive life of affected plants is shortened. Grapevine decline is present throughout Castilla y León (Spain). In the present work, the fungi potentially associated with grapevine decline were isolated and identified. Botryosphaeria-like spp., Phaeomoniella chlamydospora and Phaeoacremonium spp. were common. Cylindrocarpon spp. were found mainly in young plants, while Phomopsis viticola, Fomitiporia mediterranea, Eutypa lata and Stereum hirsutum were found only occasionally. Particular attention was given to the identification of the Botryosphaeria-like species, of which several were found. By comparing restriction endonuclease patterns (ITS1-NL4) and the sequences of the internal transcribed spacer fragments (ITS4-ITS5), Diplodia seriata (=B. obtusa), Diplodia mutila (=B. stevensii), Neofusicoccum parvum (=B. parva), B. dothidea, Dothiorella iberica (=B. iberica) and Dothiorella sarmentorum (=Diplodia sarmentorum) were all identified. D. seriata and D. mutila were identified on plants older than five years. The incidence of infection by “Botryosphaeria” species in young plants was very variable.